Challenges of designing for sociability to enhance player experience in Massively Multi-player Online Role-playing Games - Christou, Georgios; Law, Effie Lai-Chong; Zaphiris, Panayiotis; Ang, Chee Siang (My University, 2013)
Massively Multi-player Online Role-playing Games (MMORPGs) have become a popular leisure activity. It has been suggested that the reason for their popularity is that they offer a new ‘third-place’ for people to socialise. However, designing for sociability in these games has been shown to be a challenge. In this article, we discuss the results of an online survey that was directed towards game design researchers and professionals. We then present a subsequent discussion on the results of the survey at a Special Interest Group (SIG) held at CHI 2011. Through analysis of the findings of the survey and the discussion, we propose six requirements that facilitate the design of MMORPGs: In-game Communication, Off-game Communication, Empathy, Grouping and Rewards, World Design, and Designed Relationships. We state that it is not necessary to add all the proposed requirements in the design of such games, but we also caution that a game that does not include any of the requirements presented here cannot belong to this genre. We discuss limitations of this work, and offer future research directions that result from this work.
Keywords: Game design; User experience; Player experience; MMORPG; Sociability; Social games